Drones in Insect Pest Management: Transforming Agriculture with Precision Technology - Asritha, Chava; Ramesha, N. M.; Satwika, Maharaj (Chronicle of Bioresource Management, 2024)
Precision agriculture depends heavily on crop health monitoring, and drones play an essential role in detecting on-site issues and enabling timely corrective actions. In India, where labour and technical expertise are often limited, drones present a valuable solution for advancing smart farming practices. Insect pests remain a significant challenge, reducing food grain production worldwide. In India, small and marginal farmlands complicate pest management, as spraying one field can often drive pests to neighbouring areas, making consistent control difficult. Although drones offer high-resolution capabilities for precise, site-specific farm management, their broader adoption faces regulatory restrictions. These guidelines, set globally, limit the potential for drones in agriculture. Addressing these regulatory hurdles could unlock the full benefits of drones, enhancing productivity and pest management. By facilitating drone usage, India could make significant strides in agricultural efficiency, empowering farmers to better combat pests and boost crop yields across diverse landscapes.